A randomized, placebo-controlled clinical trial evaluating of a mouthwash containing Sambucus williamsii var. coreana extract for prevention of gingivitits - Yu-Rin Kim; Seoul-Hee Nam (Scientific Reports, 2022)
Abstract The purpose of this study is to verify the clinical applicability by applying a mouthwash containing Sambucus williamsii var. coreana extract for preventing periodontal disease. A randomized, double-blind, placebo-controlled study was conducted on 64 patients, excluding those with insufficient data, who visited M dental clinic located in Busan, Korea. Thirty-two people were assigned respectively to the saline solution gargle group and the Sambucus williamsii var. coreana extract gargle group to conduct the O'Leary index, plaque index (PI), gingival index (GI), and subgingival plaques. For the homogeneity of the two groups, scaling was carried out one week before the experiment, and the participants were taught for oral care to conduct during the study period. SPSS 24.0 for Windows (IBM Corp., Armonk, NY, USA) was used to compare the saline solution gargle group and the Sambucus williamsii var. coreana extract gargle group as well as to analyze Baseline (before gargle application), Treatment (immediately after gargle application), and After 5 Days (5 days after gargle application). There was a significant difference in the O'Leary index, PI, GI and subgingival plaques after Treatment and After 5 days (p < 0.05). Also, the periodontal-related indexes improved as the application time increased in the Sambucus williamsii var. coreana extract gargle group. The antibacterial effect was also shown for gram-positive bacteria and gram-negative bacteria in subgingival plaques as the application time increased. The use of the mouthwash containing Sambucus williamsii var. coreana extract was found to be effective for oral periodontal-related indicators and bacteria causing periodontal disease. Therefore, using a mouthwash containing Sambucus williamsii var. coreana extract, a natural drug, will possibly maintain healthy periodontal health by inhibiting and preventing the progression of periodontal disease.